ANALISIS KANDUNGAN AKRILAMIDA DALAM UBI GORENG YANG DIJUAL DI KOTA MANADO MENGGUNAKAN KROMATOGRAFI CAIR KINERJA TINGGI (KCKT) - Sengke, Clara A.; Citraningtyas, Gayatri; Wehantouw, Frenly (PHARMACON, 2013)
ABSTRACT Acrylamide is caused by a high temperature (more than 1200C) in the food that contains high carbohydrate. Acrylamide was classified as senyawa that caused cancer or have high potention as carcinogenic compound in the human body. Junk food which mostly eaten by people is fries. The aims of this research were to identify how much acrylamide was contains in sweet potato fries that has been sell at Manado City using High Performance Liquid Chromatography (HPLC) method. The samples that has been identified is came from 7 store in 7 sub district at Manado City. In this research, the acrylamide were analysed with High Performance Liquid Chromatography using Shim-Pack VP-ODS (4,6 x 250 mm) column, comparison of mobile phase acetonitrile and phosphate acid 11,45 mM (20 : 80), flow rate 1 ml/minute and at wave length 210 nm. The result shows acrylamide found in sweet potato fries with retention time Â±3,311 minutes. Acrylamide that contains in sweet potato fries which has been sell in Manado City were 118,54-866,75 Î¼g/kg. Acrylamide level that found in sweet potato fries is still under lethal dose. Keywords : Acrylamide, sweet potato fries, HPLC, Manado